2014
DOI: 10.1007/s10585-014-9679-9
|View full text |Cite
|
Sign up to set email alerts
|

A role for STEAP2 in prostate cancer progression

Abstract: Prostate adenocarcinoma is the second most frequent cancer worldwide and is one of the leading causes of male cancer-related deaths. However, it varies greatly in its behaviour, from indolent non-progressive disease to metastatic cancers with high associated mortality. The aim of this study was to identify predictive biomarkers for patients with localised prostate tumours most likely to progress to aggressive disease, to facilitate future tailored clinical treatment and identify novel therapeutic targets. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 31 publications
6
71
0
Order By: Relevance
“…STEAP2 (Seven Transmembrane Epithelial Antigen of the Prostate 2) is a gene primarily expressed in the prostate and the ovary is the only other area with a significant expression [36]. e roles of STEAP2 in OvCa may be similar to prostate cancer in which STEAP2 was observed to be upregulated and associated with advanced stage and Gleason score [37,38]. e overexpression of STEAP2 induced the normal prostate cells to gain an ability to migrate and invade [36] while the knockdown of STEAP2 significantly reduced proliferation and migration of prostate cancer cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…STEAP2 (Seven Transmembrane Epithelial Antigen of the Prostate 2) is a gene primarily expressed in the prostate and the ovary is the only other area with a significant expression [36]. e roles of STEAP2 in OvCa may be similar to prostate cancer in which STEAP2 was observed to be upregulated and associated with advanced stage and Gleason score [37,38]. e overexpression of STEAP2 induced the normal prostate cells to gain an ability to migrate and invade [36] while the knockdown of STEAP2 significantly reduced proliferation and migration of prostate cancer cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the tsDMRs are strongly overrepresented in developmental gene families and genes involved in endocrine hormone secretion, such as TBX3 (Holterhus et al 2007;Beukers et al 2015), suggesting that they are associated with functional roles in cancer progression. Indeed specific tsDMRs were found in known tumor suppressor genes (for example, EHF [Albino et al 2012] and MCC [KohonenCorish et al 2007]) and oncogenes (for example, STEAP2 [Whiteland et al 2014]). Collectively, the tsDMRs suggest a convergent malignant epigenetic pathway across cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The level of STEAP‐1 expression in LNCaP cell is higher than that in PC3 cells; thus, the LNCaP xenograft model and PC3 xenograft model were created, respectively, to confirm the conjugation of STEAP‐1–targeted SonoVue microbubbles and tumors in vivo. We found that the amount of improvement of PI and AUC by STEAP‐1–targeted SonoVue microbubbles in LNCaP xenograft models were significantly higher than those in the PC3 xenograft models, which are in agreement with the levels of STEAP‐1 expression in these cell lines.…”
Section: Discussionmentioning
confidence: 99%